Estudo analítico da avaliação de desempenho dos alunos do curso de especialização em Saúde da Família UNA-SUS/Unifesp - Almeida, Lucy Ferreira de [UNIFESP] (2018)
The Permanent Education in Health - EPS aims to transform the work environment into primary care as a learning space. To better understand the effectiveness of the UNA-SUS / UNIFESP Family Health Specialization course, we investigated the coherence between the evaluative process, the egress profile and the pedagogical proposal of the course. When analyzing the process of evaluation of the performance of the student of Specialization in Family Health UNA-SUS / UNIFESP, we map the processes of evaluation in Distance Education - EaD in the health area. We describe the evaluation processes and identify the instruments for evaluating students' performance in the course. We also identify students' perceptions about the evaluative process and verify the coherence between the process and the competencies for egress performance. The proposals of the discussion forums are consistent with the theme of the complex cases addressed and it is the female students who most recognize the contribution of the forum to reflect on their professional practice. We used a quantitative research that carried out a descriptive study about the coherence between the evaluative process, the egress profile and the pedagogical proposal of the course. The questionnaire was organized with objective questions and two open questions, all responses were anonymous. In the process of checking the structure of the course, the coherence between the evaluation process and its proposals, we note that the evaluation happens to the course logo and is not identified by the students only as the evaluation at the time of the face-to-face meeting, however the students of older and with a higher degree of training are those who most recognize their contribution to identifying changes in the professional profile. We verified the contributions of the evaluation process to the construction of professional competences and to the professional practice, mainly in the communication with the user, where the significant association with the nationality was evidenced, since the Cuban students were the ones that pointed out improvements in communication with the team, indicating here an opportunity for adaptation or cultural learning.